The Role Of New Zealand Social Culture In Conflict Resolution - Avida Mileaningrum; Eri Radityawara Hidayat; Endro Legowo; Pujo Widodo; Achmed Sukendro (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
New Zealand is a country with cultural diversity and multiculturalism principles. New Zealand's social culture also plays an important role in resolving conflict by creating spaces for open and inclusive dialogue. The principles of "manaakitanga" (hospitality), "whanaungatanga" (kinship relations), and "tikanga" (Maori cultural principles) play a role in shaping patterns of social interaction that are mutually respectful and help create an environment that supports conflict resolution processes. This journal aims to analyze cultural diversity as it shapes the country's unique approach to conflict resolution as well as patterns of multicultural education in New Zealand in fostering understanding and tolerance between cultures. By understanding how New Zealand's social culture plays a role in conflict resolution, we can draw valuable lessons to apply them in a wider global context. The role of New Zealand's social culture in overcoming conflict is by Fostering Understanding and Empathy, Encouraging Social Cohesion, Facilitating Intercultural Dialogue, Implementing Inclusive Policies and Laws, Improving Education and Cultural Awareness. Overall, multicultural education in New Zealand plays an important role in promoting intercultural understanding and tolerance.